"Prevotellamassilia timonensis, " a new bacterial species isolated from the human gut. (September 2016) - Ndongo, S.; Lagier, J.-C.; Fournier, P.-E.; Raoult, D.; Khelaifia, S.
Abstract: We describe here the main characteristics of "Prevotellamassilia timonensis" gen. nov., sp. nov., strain Marseille-P2831 T (CSUR P2831), a new member of the Prevotellaceae family that was isolated from stool samples from a 45-year-old patient.